Strategy for Developing Religious Character through the Al-Qur'an Education Park Program at MI Tholabuddin Gandusari Blitar - Khusnul Khamidah; Binti Maunah (PGMI IAIN Lhokseumawe, 2023)
This study aims to analyze strategies for shaping religious character through the Al-Qur'an Education Park program. The research was conducted at MI Tholabuddin Gandusari Blitar. This study uses a qualitative approach to field research. Data collection techniques with in-depth interviews, observation, and documentation. The primary data source taken was the head of the madrasa, the coordinator of the Al-Qur'an Education Park, and the deputy head of curriculum, teachers, and students. Data analysis by collecting data, reducing data, presenting data, and concluding research results. The focus of the research is on learning, learning methods, and character religious building through the Al-Qur'an Education Garden program. Based on the results of the study, it can be concluded: (1) The learning of the Al-Qur'an educational garden program in forming religious character is reading and writing the Al-Qur'an with adjustments to learning materials according to the level of student abilities; (2) The learning method for the Al-Qur'an educational garden program is the tactile method with the implementation of learning using the drill method and the sorogan method; (3) Instilling religious character through the Al-Qur'an educational garden program with habits such as inculcating the morning creed, congregational prayers, time discipline, and exemplary teachers.